2015
DOI: 10.1007/s10895-015-1520-6
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, Characterization, DNA Binding, DNA Cleavage and Antimicrobial Studies of Schiff Base Ligand and its Metal Complexes

Abstract: A series of Cu(II), Ni(II), Co(II), Mn(II) and Zn(II) complexes have been synthesized from the Schiff base ligand L. The Schiff base ligand 4-chloro-2-((4-oxo-4H-chromen-3yl) methylene amino) benzoic acid (L) has been synthesized by the reaction between chromone-3-carbaldehyde and 4-chloro-2-amino benzoic acid. The nature of bonding and geometry of the transition metal complexes as well as ligand L have been deduced from elemental analysis, FT-IR, UV-vis, (1)H NMR, (13)C NMR, ESR spectral studies, mass, magnet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(13 citation statements)
references
References 38 publications
0
8
0
Order By: Relevance
“…In this study, SBD2 and SBD4 showed enhanced inhibitory activities against the planktonic SA and MRSA, possibly due to complexation, improved permeability and increased molecular weight [ 13 ]. Other than S. aureus , studies have also shown that Schiff base copper complexes have enhanced antimicrobial ability against Enterococcus faecalis , E. coli , Salmonella typhi , Klebsiella pneumoniae , P. aeruginosa and B. subtilis [ 7 , 14 16 ].…”
Section: Discussionmentioning
confidence: 99%
“…In this study, SBD2 and SBD4 showed enhanced inhibitory activities against the planktonic SA and MRSA, possibly due to complexation, improved permeability and increased molecular weight [ 13 ]. Other than S. aureus , studies have also shown that Schiff base copper complexes have enhanced antimicrobial ability against Enterococcus faecalis , E. coli , Salmonella typhi , Klebsiella pneumoniae , P. aeruginosa and B. subtilis [ 7 , 14 16 ].…”
Section: Discussionmentioning
confidence: 99%
“…12) show a which was shown by the antibacterial and . The enhancement of C=N-group and metal ion in complexes [41]. This enhanced antimicrobial activity nature of metal complexes was demonstrated by Overtone [42] and the chelation Tweedy [43].…”
Section: Antimicrobial Activitymentioning
confidence: 99%
“…12) show a zone of inhibition area which was shown by the test compounds against the antibacterial and antifungal strains. The enhancement of antimicrobial activity is due to -C=N chelation effect with a metal ion in complexes [41]. This enhanced antimicrobial activity nature biological screening activities of Schiff base ligands and their complexes were investigated against bacterial and fungal strains.…”
Section: Antimicrobial Activitymentioning
confidence: 99%
“…8, it is found that the activity of imine ligand is enhanced when coordinated to the metal ions. The presence of imine group (-C=N) and chelation effect with central metal enhances the anti-pathogenic actions [40]. Moreover, it has been already proved that the ligand contains nitrogen and oxygen donor systems might restrain enzyme production, since the enzymes which require these group for their activity appear to be especially more susceptible to deactivation by the metal ion upon chelation.…”
Section: Anti-pathogenic Screeningmentioning
confidence: 99%